2022
DOI: 10.1088/1361-665x/ac7b58
|View full text |Cite
|
Sign up to set email alerts
|

Multi-physical modeling and fabrication of high-performance IPMC actuators with serrated interface

Abstract: Ionic Polymer-Metal Composite (IPMC) has been widely recognized as a promising and representative candidate of soft intelligent materials actuated under low voltage. During recent few years, the importance of the electrode/substrate interface received growing attention for the research on both the ion-based mass transport modeling and practical performance manipulation of ionic electro-active actuators. In this paper, based on a macroscopic serrated interface morphology, the influences of the interface were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…After model simulation, it is found that the newly proposed crenellated structure can significantly improve the mechanical properties of IPMCs compared with the traditional structure, and the model can be used to assist the development of IPMCs. Inspired by the research of Chang et al [ 121 ] Rao et al [ 122 ] proposed an IPMC with a simple preparation process and a serrated electrode interface. Model simulations and experiments have shown that the new structure of IPMCs has high‐performance electroactive displacement.…”
Section: Physical‐based Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…After model simulation, it is found that the newly proposed crenellated structure can significantly improve the mechanical properties of IPMCs compared with the traditional structure, and the model can be used to assist the development of IPMCs. Inspired by the research of Chang et al [ 121 ] Rao et al [ 122 ] proposed an IPMC with a simple preparation process and a serrated electrode interface. Model simulations and experiments have shown that the new structure of IPMCs has high‐performance electroactive displacement.…”
Section: Physical‐based Modelsmentioning
confidence: 99%
“…The relationship between input voltage and output curvature is given Rao et al, 2022, [122] Ion and water Diffusion  Swelling stress Based on the model, the effects of interface area and excision volume on zigzag IPMC are analyzed Models based on thermodynamic theory…”
Section: Diffusion and Convectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there are few reports on the growth simulating of DIEs inside IPMC, which leads to the lack of intuitive understanding of DIEs growth. So the existing growth simulation is difficult to guide the preparation process of IPMC [1,13,21].…”
Section: Introductionmentioning
confidence: 99%